STRUCTURAL AND SEMANTIC FEATURES OF TITLES IN NEWSPAPER AND FICTION TEXTS - Babayeva Iroda (Western European Studies, 2025)
This article examines the structural and semantic features of titles in newspaper and fiction texts, highlighting their linguistic, cultural, and functional dimensions. Titles serve as a crucial gateway to the content of any text, guiding readers’ interpretations and expectations. Drawing on contemporary linguistic theories and a comparative analysis of selected examples, the study investigates how titles function differently in the two genres. The findings reveal that newspaper titles are predominantly concise and informative, often using stylistic devices to capture attention, whereas fiction titles are characterized by their ambiguity and layered meanings, aiming to evoke curiosity and emotional resonance. These distinctions underline the unique communicative goals of each genre
Keywords: structural features; semantic features; newspaper titles